Unlocking Potential: Addressing Societal and Economic Barriers for Qatari Youth in the Tourism and Hospitality Sector - Al-Mohannadi, Noora (Journal of Ecohumanism, 2025)
This quantitative research examines the factors discouraging Qatari youth from pursuing careers in the tourism and hospitality sector. It explores socio-cultural and industry-specific barriers, evaluates the effectiveness of government and private initiatives supporting local employment in the field, and proposes strategies to enhance the sector's appeal to Qatari youth. The findings reveal that societal attitudes play a significant role in shaping career choices, with 31% of respondents perceived a lack of community acceptance and 30.3% expressing uncertainty about societal openness to such roles. Many participants also have associated hospitality jobs with a negative impact on self-esteem. Additionally, 17% cited religious concerns, believing that Islam does not endorse such professions. Beyond societal influences, financial and occupational factors contribute to the reluctance of Qatari youth to enter the hospitality industry. Low financial incentives and demanding working conditions—such as long hours and high-pressure environments—were key deterrents. Compared to lucrative sectors like oil, gas, and banking, hospitality careers offer fewer financial benefits and limited opportunities for professional advancement, making alternative industries more attractive to Qatari job seekers.